Evaluasi Usability Sistem Aplikasi Mobile JKN Menggunakan Use Questionnaire - Lubis, Baginda Oloan; Salim, Agus; Jefi, Jefi (STMIK Palangkaraya, 2020)
This study aims to find out how superior and important is the application of information technology to produce an information system that is useful for answering user needs, by evaluating and analyzing information systems that have been embedded on the smartphone (smartphone) of the user who uses. Where the intended application is Mobile JKN (BPJS Health Application). The analysis was carried out to recognize the strengths and weaknesses of the system used by the user by measuring the usability of the system using the Use Questionnaire, in which there are several aspects of usability measurement according to IDO, namely efficiency, effectiveness and satisfaction, where these points become a reference for evaluating and analyzing an information system.The results of this study will show that there are several advantages or strengths of the system that can support the development and progress of this application, but the results of this study also show the weaknesses and weaknesses of the system, so that the existing system needs to be improved or improved towards a better direction